Suppuration as diagnostic criterium of peri‐implantitis. Issue 2 (21st August 2020) - Monje, Alberto; Vera, Maria; Muñoz‐Sanz, Agustín; Wang, Hom‐Lay; Nart, José
Abstract: Background: Suppuration (SUP) as a diagnostic parameter for monitoring dental implants is not yet well understood. The retrospective clinical and radiographic study was therefore performed to investigate the patient, implant, and site characteristics among individuals exhibiting SUP. Methods: Demographic characteristics and clinical parameters were recorded. Radiographic features were analyzed using cone‐beam computed tomography. Peri‐implantitis was defined based on the consensus report of Workgroup 4 of the 2017 World Workshop on the Classification of Periodontal and Peri‐Implant Diseases and Conditions: probing depth (PD) ≥6 mm, presence of bleeding and/or SUP on gentle probing, and radiographic marginal bone loss (MBL) ≥3 mm. SUP was graded according to profuseness (dot versus line/drop) and time after probing (≥15 seconds versus <15 seconds after probing versus spontaneous). Simple binary logistic regression models were estimated using generalized estimation equations to explain the probability of SUP based on demographic, clinical, and radiographic variables. Results: A total of 111 eligible patients (nimplants = 501) were assessed. Of them, 57 (nimplants = 334) were diagnosed with peri‐implantitis according to the established case definition, and of these individuals, 31 (nimplants = 96) presented SUP. Therefore, the prevalence of SUP was 27.92% in the total sample size and 54.38% in peri‐implantitis patients. Overall, 28.74% implants displayed SUP within patients with peri‐implantitis. SUP was more frequently found at buccal sites (51%) and proved less prevalent at mesio‐lingual sites (16.7%). Defect morphology (OR = 6.59; P = 0.004), PD (OR = 1.63; P = 0.024), and MBL (OR = 1.35; P = 0.010) were significantly associated with the presence of SUP. Likewise, defect morphology ( P = 0.02), PD ( P = 0.003), and MBL ( P = 0.01) were significantly correlated with the grade of SUP. Conclusion: The presence and grade of SUP are associated with peri‐implant bone loss, probing depth, and defect morphology in patients with peri‐implantitis.